Reuse of food waste as animal feed in Sri Lanka - Jayathilake, Nilanthi; Aheeyar, Mohamed M. M.; Drechsel, Pay (2021)
The use of food waste (FW) from food services as animal feed through informal agreements has been in practice for many years in Sri Lanka. However, data to show the scale of this practice are inadequate. This paper aims to study the extent of FW diverted to piggeries and the opportunities and challenges in reusing FW as animal feed. The data were collected via telephonic survey from 24 piggery farmers in the Western Province in May 2020. Results revealed that 50% of farmers were rearing 100-300 pigs. Farmers used FW as a major feed source to satisfy 82% of total feed requirement on an average. About 40% of the farmers collected the FW from multiple sources such as hotels, restaurants and canteens. Given that the piggery farms are located in peri-urban areas, the average distance traveled by the farmers is 38 km up and down which indicated the value of FW for them. FW was supplied mostly free of charge; however, 26% of the farmers pay LKR 2 to 40/kg when supplied by intermediaries. FW was collected daily, and the amount collected by the farmers varies 50 to 10000 kg/day depending on demand and supply, with 75% of farmers collected less than 1000 kg/day.